Electronic Module with Scientific Approach in Training Students’ Science Process Skills on Solid Elasticity Learning Material - Emy Nur Juliana; Zainuddin Zainuddin; Dewi Dewantara (Universitas Lambung Mangkurat, 2023)
One of the skills in physics learning required to face the challenges of the 21st century is science process skills. Science process skills are used to discover previous laws, concepts, principles, and theories and refute previous findings. Therefore, science process skills need to be developed complexly in teaching materials in the form of an electronic module. This research aims to produce a valid, practical, and effective electronic module with a scientific approach to the material of solid elasticity that can be used to train students' scientific process skills. The research and development (R&D) method was employed on twenty students from class XI MIPA 2 SMA Negeri 12 Banjarmasin using the ADDIE development model. The data was collected through electronic module validation instruments, learner questionnaires, learning achievement tests, and the achievement of science process skills. The research findings showed that (1) The validation of the electronic module was rated as good with an average score of 3.14; (2) The practicality of the electronic module obtained a practical category with an average score of 3.35; (3) The effectiveness of the electronic module was rated as moderate with an N-gain score of 0.63; (4) The achievement of students' science process skills reached good category with an average score of 3.15. Thus, the developed electronic module can train science process skills and be used in learning activities.Â